1975
DOI: 10.1037/h0076395
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of behaviors elicited by electrical brain stimulation in dorsal brain stem and hypothalamus of rats.

Abstract: Four brain-stimulation phenomena elicited from both dorsal brain stem and hypothalamic sites were investigated with the following results: (a) intracranial self-stimulation rate-intensity functions for dorsal brain stem and hypothalamic sites yielded very high (over 1,000 responses/15 min.) to moderate (201-500 responses/15 min.) response rates; (b) d-amphetamine produced higher response rates than either Z-amphetamine or saline at both dorsal brain stem and hypothalamic sites, indicating that noradrenergic do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
6
0

Year Published

1976
1976
1982
1982

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 26 publications
3
6
0
Order By: Relevance
“…This was true at all C-T intervals tested and regardless of which site was stimulated first. These results are also in accord with previously published data (Ackermann et al, 1973;Coons et al , 1976;Ellman et al , 1975;German & Holloway, 1973;Ungerleider & Coons , 1970) and suggest that the LC and HYP interact neurophysiologically. Third, these differences, and indeed the interactions themselves, cannot be attributable to such nonspecific factors as passive current spread, since the monophasic pulse pair technique was employed in the present study.…”
Section: Rat67gsupporting
confidence: 83%
See 2 more Smart Citations
“…This was true at all C-T intervals tested and regardless of which site was stimulated first. These results are also in accord with previously published data (Ackermann et al, 1973;Coons et al , 1976;Ellman et al , 1975;German & Holloway, 1973;Ungerleider & Coons , 1970) and suggest that the LC and HYP interact neurophysiologically. Third, these differences, and indeed the interactions themselves, cannot be attributable to such nonspecific factors as passive current spread, since the monophasic pulse pair technique was employed in the present study.…”
Section: Rat67gsupporting
confidence: 83%
“…For these latter two hypotheses, the MFB and LC must necessarily share common characteristics given the symmetry of LC-MFB interactions. Pharmacological data support this notion, since d-but not l-amphetarnine enhances both LC and MFB at low doses (Ellman et al, 1975;Ellman, Ackermann, Bodnar, Jackler, & Steiner, 1976;Phillips, Brooke, & Fibiger, 1975;Phillips & Fibiger, 1973;Stephens & Herberg, 1975), while both isomers nearly equipotently enhance DFLH ICSS at the same doses (Stephens & Herberg, 1975).…”
Section: Rat67gsupporting
confidence: 56%
See 1 more Smart Citation
“…Yet both sets of loci are similar in ICSS responding as 'a function of changes in CoT interval. Similarly, DPT ICSS placements are differentially separable from MPG ICSS placements in reactivity to d-and I-amphetamine, in ICSS responding following forebrain lesions and in supporting enhanced ICSS responding when paired with various diencephalic ICSS loci (Bodnar et al, 1975;Clavier & Corcoran, 1976;Ellman et ai., 1976;Phillips et ai., 1975;Phillips & Fibiger, 1973;Bodnar et aI., Note 2). Yet both sets of loci are similar in ICSS resptmding as a function of changes in CoT intervai.…”
Section: Discussionmentioning
confidence: 99%
“…Becker and Reid (Note 2) demonstrated that 20 sec of 20-microA 60-Hz sine waves, programmed periodically, reduced pressing for lowintensity ICS. Consequently, the parameters oflCS used in many studies (e.g., Ellman, Ackerman, Bodnor, Jackler, & Steiner, 1975) can modify the tissue of ICS. This effect could confound the conclusions that might be drawn, and it was thought that modification of tissue by the higher intensities of ICS might, in tum, modify drug action.…”
Section: Discussionmentioning
confidence: 99%